Modern cryptography : applied mathematics for encryption and information security - Easttom, Chuck (Online access with DDA: Askews (Maths), 2016)
This comprehensive guide to modern data encryption makes cryptography accessible to information security professionals of all skill levels, with no mathematical expertise required.